2022
DOI: 10.1002/adma.202108621
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Selectivity and “Order‐in‐Disorder” Engineering in Carbon for Durable and Fast Potassium Storage

Abstract: Defect‐rich carbon materials possess high gravimetric potassium storage capability due to the abundance of active sites, but their cyclic stability is limited because of the low reversibility of undesirable defects and the deteriorative conductivity. Herein, in situ defect‐selectivity and order‐in‐disorder synergetic engineering in carbon via a self‐template strategy is reported to boost the K+‐storage capacity, rate capability and cyclic stability simultaneously. The defect‐sites are selectively tuned to real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 70 publications
2
82
0
Order By: Relevance
“…In addition, C–S–C also exhibited better reversibility than C–SO x –C. 54 The above results also confirm that the NSPC700 anode delivered a higher reversible capacity due to its rich N and S heteroatoms in the specific formations (N-5, N-Q, and C–S–C).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, C–S–C also exhibited better reversibility than C–SO x –C. 54 The above results also confirm that the NSPC700 anode delivered a higher reversible capacity due to its rich N and S heteroatoms in the specific formations (N-5, N-Q, and C–S–C).…”
Section: Resultssupporting
confidence: 66%
“…It is shown that C-S-C was almost transformed into -K 2 S x , while only a part of C-SO x -C was combined with K ions aer potassiation (Table S3 †). In addition, C-S-C also exhibited better reversibility than C-SO x -C. 54 The above results also conrm that the NSPC700 anode delivered a higher reversible capacity due to its rich N and S heteroatoms in the specic formations (N-5, N-Q, and C-S-C).…”
Section: Resultsmentioning
confidence: 59%
“…The main reason for the high number of defects is that a lot of heteroatom dopants are lost during high-temperature pyrolysis. 45 All the samples exhibit type-IV N 2 adsorption–desorption isotherms with a strip hysteresis loop over a wide relative pressure range (Fig. 1H).…”
Section: Resultsmentioning
confidence: 96%
“…Compared with the recent studies on carbon-based PIBs anodes (Figure 2j), the OLSC exhibits an excellent rate performance and stability while ensuring a lower voltage plateau. [11,27,[37][38][39][40][41] The full-cell tests of OLSC further proved the practical application of OLSC in potassium-ion batteries. As shown in Figure S7 (Supporting Information), the K 2 MnFe(CN) 6 ||OLSC full cell showed a suitable voltage plateau about 1.5 V, and a discharge capacity of 78.6 mAh g -1 after 100 cycles.…”
Section: Electrochemical Performance Of Olscmentioning
confidence: 99%